Badminton singles simulation from the data obtained in physical education class - Suda, K.; Nagayama, T.; Arai, T.; Nozawa, M. (The impact of technology on Sport II, 2008)
Game simulation is useful to make a training program. Coaches imagine matches before a tournament in their brain. This process is necessary when they plan for practice. In this study, we tried badminton singles simulation in physical education class. Students played singles matches and all the flight data were obtained. The court was divided into ten areas. Probabilties of players` selection of their flight from all the area were calculated. Badminton game simulation was done among the students. The players shots were determined with randomly picked number and the flight selection probability from the all the court areas. Twenty eight matches were played on computer. The results were compared with real matches. The results of twenty six matches were the same as the real matches. This suggests that the computer simulation of the badminton game in physical education class is successful.